2013
DOI: 10.1111/bju.12171
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and complications after transperineal bulboprostatic anastomosis for posterior urethral strictures resulting from pelvic fracture: a retrospective study from a urethral referral centre

Abstract: Objective• To describe the complications of transperineal end-to-end anastomotic urethroplasty in patients with posterior urethral strictures resulting from pelvic fracture. Materials and Methods• A total of 573 patients, who underwent bulboprostatic anastomosis for posterior urethral strictures, were enrolled in this study. Distraction defects were measured using retrograde urethrography combined with voiding cysto-urethrography. • All patients underwent perineal excision and primary anastomotic urethroplasty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…If the length of the urethra is inadequate, the horn of the penis must be split and the lower limb of the pubis must be cut off. According to the investigation data collected by Fu et al [6] on posterior urethral stricture after pelvic fracture, the occurrence rate of erectile dysfunction (ED) in patients after pelvic fracture was 85%. However, the ED occurrence rate after urethroplasty was 86%, indicating that no considerable difference occurred between ED occurrence rate before operation and that after operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the length of the urethra is inadequate, the horn of the penis must be split and the lower limb of the pubis must be cut off. According to the investigation data collected by Fu et al [6] on posterior urethral stricture after pelvic fracture, the occurrence rate of erectile dysfunction (ED) in patients after pelvic fracture was 85%. However, the ED occurrence rate after urethroplasty was 86%, indicating that no considerable difference occurred between ED occurrence rate before operation and that after operation.…”
Section: Discussionmentioning
confidence: 99%
“…Although some research showed that this conventional operation method generally does not affect sexual function after operation [6], it damages the surrounding blood vessels and tissue of the posterior urethra, and thus may also disrupt the erectile function to some extent. In this study, the non-transecting anastomotic urethroplasty was put into preliminary clinical practice, and the related indexes concerning operation condition, urinating condition after operation, and erectile function were evaluated to identify the influence of this method on the urination and sexual function of patients with posterior urethral stricture after operation.…”
Section: Introductionmentioning
confidence: 99%
“…71 Fu et al reported that 88% (447/ 510) of the men in a retrospective study at a referral center were continent after delayed urethroplasty. 87 However, the external sphincter can be damaged in complex urethral disruptions or during total excision of scars for even a short urethral stenosis. Urinary continence in such cases depends on bladder neck function.…”
Section: Incontinencementioning
confidence: 99%
“…Postoperative recurrence of stricture is also a problem with this procedure. 13 Success rate of perineal anastomotic urethroplasty is 82% to 95% in different studies. 14 Since Webster and Roman reported results of trans-perineal anastomotic urethroplasty for posttraumatic urethral disruption (currently termed as PFUI) with very high success-rate (96%), the method has been considered a gold standard surgery.…”
Section: Introductionmentioning
confidence: 99%